2000
DOI: 10.1038/sj.gt.3301322
|View full text |Cite
|
Sign up to set email alerts
|

Virus-like gene transfer into cells mediated by polyoma virus pseudocapsids

Abstract: Mouse polyoma virus-like particles (or pseudocapsids) are composed solely of recombinant viral coat protein. They can interact with DNA and transport it to cells, resulting in gene expression both in tissue culture and in mice. We demonstrate that DNA transfer in vitro depends on partial packaging of DNA within the virus-like capsid. Cell surface sialic acid residues and an intact microtubule network, required for viral infectivity, are also necessary for pseudocapsidmediated gene expression from heterologous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
34
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 44 publications
4
34
0
Order By: Relevance
“…VLPs may only require the primary HSPG receptor for internalization. Two routes of particle uptake and differences in the uptake mechanisms of virions and VLPs were also observed for polyomaviruses, resulting either in nuclear targeting or, as for the bulk of empty VLPs, in lysosomal degradation (26).…”
Section: Discussionmentioning
confidence: 99%
“…VLPs may only require the primary HSPG receptor for internalization. Two routes of particle uptake and differences in the uptake mechanisms of virions and VLPs were also observed for polyomaviruses, resulting either in nuclear targeting or, as for the bulk of empty VLPs, in lysosomal degradation (26).…”
Section: Discussionmentioning
confidence: 99%
“…First, and most importantly, the position of fluorescently labeled particles can be related directly to the topography of the cell surface. Previously, this had only been possible in the context of markers such as plasma membrane proteins, cytoskeleton, or lipid dyes (16,22,23). Such studies can result in artifacts if the markers change during the uptake process and, as the surface of most cells is dynamic, determining whether particles have passed through the membrane or have moved with the membrane as it undulates is extremely difficult.…”
Section: Discussionmentioning
confidence: 99%
“…The protein nanospheres encapsidate 1-2 kb of the plasmid DNA whereas the remainder loosely associates with the outside of the VLP structure (14,15). These particles enter cells by both receptor-dependent and -independent routes, but only the former is productive for gene transfer (16). Thus, the fate of the VLPs may be determined by their interaction with the cell membrane, making VLPs an ideal model to test our system.…”
mentioning
confidence: 99%
“…A study on transfection by recombinant polyoma virus coat proteins assembled with DNA observed that these complexes entered at least two pathways: one that was clathrin-mediated and microtubule dependent, leading to transfection, and another that was actin mediated and nonproductive for transfection. 186 Microtubule depolymerization by nocodazole nearly completely abolished gene transfer, whereas actin depolymerization by cytochalasin D did not. While two pathways of trafficking were observed, the bulk of material entering cells translocated by the actin-mediated route.…”
Section: Lipoplexes a Study On Lipoplex Transfection Hasmentioning
confidence: 98%